Small molecule Mcl-1 inhibitor for triple negative breast cancer therapy - Dong, Shengli; Alahari, Suresh K. (Frontiers in Cell and Developmental Biology, 2024)
Apoptosis is an evolutionarily conserved cell death pathway that plays a crucial role in maintaining tissue homeostasis, orchestrating organismal development, and eliminating damaged cells. Dysregulation of apoptosis can contribute to the pathogenesis of malignant tumors and neurodegenerative diseases. Anticancer drugs typically possess the capacity to induce apoptosis in tumor cells. The Bcl-2 protein family, consisting of 27 members in humans, serves as the key regulator of mitochondrial function. This family can be divided into two functional groups: anti-apoptotic proteins (e.g., Bcl-2, Bcl-xl, Mcl-1) and pro-apoptotic proteins (e.g., Bad, Bax). Mcl-1 exerts its function by binding pro-apoptotic Bcl-2 proteins thereby preventing apoptosis induction. Overexpression of Mcl-1 not only correlates closely with tumorigenesis but also associates significantly with resistance towards targeted therapy and conventional chemotherapy. Effective induction of apoptosis can be achieved through inhibition or interference with Mcl-1. Thus, this mini review discusses existing Mcl-1 inhibitors.